Humoral immune response to Mycobactrium tuberculosis cell wall fraction and lipoarabinomannan antigens in Bangladeshi patients with active tuberculosis - Mohiuddin, Md.; Haq, J. Ashraful (IMC Journal of Medical Science, 2017)
Background and objective: This study focused on the analysis and comparison of humoral immune response to Mycobacterium tuberculosis (MTB) cell wall fraction (CWF) and lipoarabinomannan (LAM) antigens. Methods: Sera from adult patients with active pulmonary tuberculosis and age and sex matched healthy individuals were tested for immunoglobulin (Ig) M and IgG antibodies to CWF and LAM by enzyme linked immunosorbent assay (ELISA). Results: The mean OD values of serum IgM and IgG antibodies against CWF of TB patients was not significantly (p=0.52, p=0.45) different from that of healthy control population. However, the mean OD values of serum IgM and IgG against LAM were significantly (p=0.049, p= 0.001) higher in TB cases than that of healthy individuals. Conclusion: The present study has revealed that IgM and IgG antibody to LAM may be used in serodiagnosis of TB while response to CWF in active TB case is restricted in our population. IMC J Med Sci 2016; 10(2): 58-60